Orthodontic Treatment For Patients With Diabetes: Integrating Medical Devices, Clinical Laboratory Science, Health Informatics And Consultant Orthodontist Expertise To Enhance Health Care Services Outcomes (The Review of Diabetic Studies, 2025)
Diabetes mellitus presents significant challenges for orthodontic treatment due to its widespread effects on periodontal health, bone remodeling, and soft-tissue healing. This integrative review examines how a multidisciplinary, technology-enabled approach can enhance orthodontic outcomes for patients with diabetes. Evidence from clinical, laboratory, nursing, and informatics literature reveals that diabetes increases susceptibility to periodontal inflammation, delays orthodontic tooth movement, and elevates the risk of treatment complications when glycemic control is suboptimal. Modern medical devices—including digital imaging, intraoral scanning, and controlled-force appliances—improve diagnostic precision and help mitigate biologically compromised responses. Laboratory diagnostics, particularly HbA1c and inflammatory biomarkers, were found essential for assessing treatment readiness and monitoring systemic stability. Health informatics systems support interdisciplinary communication by integrating laboratory data, imaging records, and clinical notes, thereby enabling timely interventions and coordinated care. Nursing practice further enhances treatment safety through patient education, glycemic monitoring, and reinforcement of oral hygiene behaviors. Collectively, the findings underscore that successful orthodontic management for diabetic patients depends on the integration of consultant orthodontist expertise with laboratory diagnostics, medical technologies, informatics solutions, and nursing support. This coordinated model offers a comprehensive framework for improving treatment predictability, reducing complications, and elevating the standard of orthodontic care for medically complex populations.